THE INFLUENCE OF PRODUCT FEATURES, NETWORK REACH, AND PRICE, ON THE PURCHASE DECISION OF RESIDENTS' INTERNET PACKAGES IN LINTONG NIHUTA - Posnita Sihombing; Fenny B.N.L. Tobing; Melinda Malau (Universitas Kristen Indonesia, 2022)
This study aims to determine the effect of product features, network coverage, and price on purchasing decisions. The population in this study is residents of Lintong Nihuta. The sample set is 100 respondents who use Telkomsel internet package cards. This researcher uses a random sampling technique which includes product features, network coverage, price and purchase decisions. The data analysis method used is descriptive analysis of respondents' characteristics, descriptive data includes, multiple regression analysis. The results of this study indicate that there is an effect of product features. Network coverage, and price simultaneously on the purchase decision. This is indicated by the value of Sig. of 0.000 <0.05 and F count 47.146> Ftable 2.70. Keywords: product features, network coverage, price and purchasing decisions